The analytical landscape of static and temporal dynamics in transcriptome data - Oh, Sunghee; Song, Seongho; Dasgupta, Nupur; Grabowski, Gregory (Frontiers in Genetics, 2014)
Interpreting gene expression profiles often involves statistical analysis of large numbers of differentially expressed (DEX) genes, isoforms, and alternative splicing (AS) events at either static or dynamic spectrums. Reduced sequencing costs have made feasible dense time-series analysis of gene expression using RNA-seq; however, statistical methods in the context of temporal RNA-seq data are poorly developed. Here we will review current methods for identifying temporal changes in gene expression using RNA-seq, which are limited to static pairwise comparisons of time points and which fail to account for temporal dependencies in gene expression patterns. We also review recently developed very few number of temporal dynamic RNA-seq specific methods. Application and development of RNA-specific temporal dynamic methods have been continuously under the development, yet, it is still in infancy. We fully cover microarray specific temporal methods and transcriptome studies in initial digital technology (e.g. SAGE) between traditional microarray and new RNA-seq. Keywords: RNA-seq, initial digital technology, microarray gene expression, differential expression, static and temporal dynamics